2012
DOI: 10.1017/s0033291712001341
|View full text |Cite
|
Sign up to set email alerts
|

Speed of facial affect intensity recognition as an endophenotype of first-episode psychosis and associated limbic-cortical grey matter systems

Abstract: Speed of facial affect processing presents as a candidate endophenotype of FEP. The normal association between speed of facial affect processing and cortico-limbic GM variation was disrupted in FEP patients and their relatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…There were some limitations in this study. Although Dean et al (2013) showed that diminished FAR processing speed rather than accuracy may be characteristic of FEP patients, here, we did not capture reaction times and, hence, potential intervention effects on patients' processing speed were not examined. Second, as FAR was assessed through full-intensity emotional expressions, any intervention effect on the recognition of subtle facial expressions in these patients remains to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…There were some limitations in this study. Although Dean et al (2013) showed that diminished FAR processing speed rather than accuracy may be characteristic of FEP patients, here, we did not capture reaction times and, hence, potential intervention effects on patients' processing speed were not examined. Second, as FAR was assessed through full-intensity emotional expressions, any intervention effect on the recognition of subtle facial expressions in these patients remains to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…68, 69 Shared variance between family members in brain-behavior networks implicated in fear processing is particularly interesting in light of the social context in which fear is learned, 70 as childhood adversity has been shown to either improve 71, 72 or impair fear recognition performance. 73 Comparisons between CDIs and their siblings who share adverse childhood experiences 74 may thus provide insight into compensatory mechanisms in fear processing in those siblings who do not abuse drugs, possibly elucidating sources of resilience.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of this “Behavioral PLS” is to take 2 multivariate matrices (one for behavioral variables and the other for brain variables) and find the combination of LVs from the brain and behavioral matrices that express the largest amount of common information (i.e., largest covariance) ( McIntosh and Lobaugh 2004 ; Krishnan et al 2011 ). This has been applied in studies of obsessive-compulsive disorder, autism, and psychotic disorder ( Menzies et al 2007 ; Ecker et al 2012 ; Dean et al 2013 ). In our case, this “1-group PLS” analysis identifies the set of brain voxels most correlated with the LV underlying the 3 current language measures in male adults with ASC.…”
Section: Methodsmentioning
confidence: 99%